ANALISIS STUDI KELAYAKAN KEUANGAN SENTRA PENINGKATAN PERFORMA OLAHRAGA INDONESIA (SP2OI) DI MENARA MANDIRI - Kurniawan, Reza (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to assist the Ministry of Youth and Sport's LPDUK in conducting feasibility planning for SP2OI development from various aspects such as site feasibility aspects, interior design aspects, mechanical aspects, type of business, type of service, environmental aspects, especially financial aspects and risk mitigation to be carried out by implementing activities. This research uses a business feasibility study and its methodswill be used to conduct this research is a qualitative descriptive method. The analysis showed that from various aspects, especially financial aspects, it was declared feasible.